Magnetic, Mössbauer, and Electronic Spectral Properties of Bis(1,2,4-triazole)triazolatoiron(II) Trifluoromethanesulphonate Monohydrate - Kristian H Sugiyarto (Jurnal Matematika & Sains, 2003)
Salt of [Fe(trzH)2(trz)][CF3SO3].H2O (where trzH = 1,2,4- triazole, and trz = triazolato, that is deprotonated 1,2,4-triazole anion) has been successfully isolated as white powder. Its magnetic, Mössbauer and electronic spectral properties are temperature dependent and reveal that the salt exhibits thermally spin state, singlet 1A1g ( .s)lquintet 5T2g (h.s), transition in iron(II). The transition is relatively abrupt, incomplete down to ~ 89 K and without hysteresis. The room-temperature electronic spectrum of the salt reveals a high-spin ligand field band which is split into two at about 11000 cm-1 and 13000 cm-1. At low temperature, the intensity of the high-spin ligand field band is reduced significantly and a strong low-spin ligand field band appears at about 18500 cm-1. The change in pattern of the spectrum is associated with the thermochromic behaviour, being white at room temperature but violet at the low one. The X-ray diffractogram suggests that the salt be isostructure to the corresponding hexafluorophosphate salt, [Fe(trzH)2(trz)][PF6], which is also white and high-spin at room temperature but pink-violet and low-spin at the low one.